Explore VaR implementation in the Chinese Bank Context and Risk Management Officers' Understanding - Zhou, Mo (2006)
This dissertation aims to explore the feasibility and validity of implementing Value-at-Risk (VaR) in the Chinese bank context and Risk Management Officers understanding, perception and values by the method of participant observation, interviews and questionnaires. As the existing literature indicates, Chinese financial institutions, especially Chinese banks introduce VaR for multiple objectives with discretion, but there is a gap between official objective and real practice. This dissertation will examine how VaR is applied and explore relative problems during the implementation, particularly relating to the Chinese bank context. The second focus is how the Risk Management officers at both executive and staff level evaluate VaR during the Chinese banks Risk Management reform.